Exploiting limited valence patchy particles to understand autocatalytic kinetics - Silvia Corezzi (Nature Portfolio, 2018)
Autocatalysis is common in chemistry, biophysics and material science, but existing approaches are unable to fully capture the physical mechanisms behind it. Here, the authors exploit a limited valence patchy particle model and reveal a novel kinetic effect crucially related to the presence of activation barriers.